New image encryption algorithm based on double chaotic system and compressive sensing - Yuguang YANG; Guodong CAO (网络与信息安全学报)
Image encryption technology plays an important role in today’s multimedia applications and Internet information security transmission.However, most image encryption algorithms still have problems, for example, cipher images occupied high bandwidth during transmission, image encryption speed is slow, image encryption algorithms are not associated with plain image, and there is no complete ciphertext feedback mechanism.These problems all affect the security and easy use of image encryption algorithms.In order to solve the above problems, the compressive sensing technology and chaotic system were studied, and a new image encryption algorithm based on double chaotic system and compressive sensing with plaintext association was proposed.The plaintext image association key was used to associate the plain image hash value with the Logistic chaotic system parameters.Discrete wavelet transform, was used to sparse the plain image.Then the random measurement matrix was generated by the Logistic chaos system, and the image was encrypted once by combining the compressive sensing technique and the random measurement matrix to obtain the intermediate image.The intermediate image was hashed again, and the Rucklidge chaos system initial value was associated with the plain image hash value together.The Rucklidge chaotic system and encryption algorithm were used to control the intermediate image for secondary encryption and accordingly obtain the cipher image.The encryption algorithm was a new plaintext correlation encryption algorithm, which used the image’s own pixel value to control the scrambling of the intermediate image.It also enhanced the plaintext association and established a ciphertext feedback mechanism.Simulation results and performance analysis show that the algorithm has good encryption performance.The encrypted image can be compressed according to the compression ratio, effectively reducing the size of the cipher image.Moreover, it is resistant to common attacks such as known plaintext attack, selective plaintext attack and differential attack, which is better than other common image encryption algorithms.